Novel Al/Al2O3 composite foams by direct oxidation conversion. Issue 1 (July 2020) - Chen, X; Sun, R; Betke, U; Scheffler, M
Abstract: In this paper we combined an investment casting technique and a direct oxidation conversion (DOC) method to fabricate novel Al/Al2 O3 composite foams. We treated open cellular Al foams with dense struts in oxidizing atmosphere and obtained novel Al/Al2 O3 composite foams. These novel-type foams had dense struts, and owned a ternary-layered structure within struts, which consisted of the inner layer of Al, the middle layer of α-Al2 O3 oxidation scale and the outer layer of α-Al2 O3 ceramic coating. The resulting foams were characterized with respect to micro and macro structure, phase composition and compression behaviour. Comparing with conventional reticulated porous ceramics (RPCs), the novel composite foams demonstrated a new deformation mode in compression, behaving in accumulative damages instead of catastrophic collapse, with more deformation capacity and better ductility. The DOC approach might inspire a new way to manufacture composite foams, and such foams might be alternatives to other cellular solids for specific applications.